2019
DOI: 10.5334/aogh.919
|View full text |Cite
|
Sign up to set email alerts
|

People Welcomed This Innovation with Two Hands: A Qualitative Report of an mHealth Intervention for Community Case Management in Malawi

Abstract: Introduction: Community Case Management (CCM) aims to improve health outcomes among children under five with malaria, diarrhea, and pneumonia, but its effectiveness in Malawi is limited by inconsistent standards of delivery characteristic of paper-based interventions. This may lead to negative impacts on child health outcomes and inefficient use of health system resources. This study evaluated the acceptability and impact of the Supporting LIFE Community Case Management App (SL eCCM App) by Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
4
5
0
Order By: Relevance
“…Our results add to previous qualitative studies which have shown that HSAs feel empowered using apps such as the one evaluated here (29), and that these tools might support greater adherence to CCM(21). These results support wider implementation and potentially addition of further functionalities, to support HSAs using smartphones to facilitate other tasks, such as reporting requirements or drug stocking.…”
Section: Discussionsupporting
confidence: 83%
“…Our results add to previous qualitative studies which have shown that HSAs feel empowered using apps such as the one evaluated here (29), and that these tools might support greater adherence to CCM(21). These results support wider implementation and potentially addition of further functionalities, to support HSAs using smartphones to facilitate other tasks, such as reporting requirements or drug stocking.…”
Section: Discussionsupporting
confidence: 83%
“…Our results add to previous qualitative studies that have shown that HSAs feel empowered using apps such as the one evaluated here [ 21 ] and that these tools might support greater adherence to CCM [ 32 ]. These results support wider implementation and potential addition of further functionalities to support HSAs using smartphones to facilitate other tasks, such as reporting requirements or drug stocking.…”
Section: Discussionsupporting
confidence: 81%
“…Decision support systems within these technologies can facilitate clinical decision-making and offer potential advantages over paper-based tools [ 19 , 20 ]. The potential advantages of e-CCM over paper-based CCM include shorter consultation time and a greater likelihood of correct diagnostic and treatment decisions, as noted in previous studies [ 21 , 22 ]. However, adopting mHealth tools as an adjunct (or replacement) for current paper-based assessment and reporting tools requires considerable initial and sustained investment.…”
Section: Introductionmentioning
confidence: 90%
“… 59 60 The surge of mHealth used in iCCM and other programs in which CHWs frequently participate can impact the data collection burden on CHWs, as well as dependency on hardware that may not always operate effectively. 61 62 Visibility and visualisation of data, especially at lower levels, have the potential to change the way stakeholders use information to make decisions and influence community understanding of program impacts. 63 64 A comprehensive M&E plan is necessary to track and measure overall program performance.…”
Section: Resultsmentioning
confidence: 99%
“…Critical to overcoming commonplace bottlenecks of evaluation is ensuring that the data elements actually exist to calculate the indicators needed for decision-making and that they are organised in a format conducive to extracting information 59 60. The surge of mHealth used in iCCM and other programs in which CHWs frequently participate can impact the data collection burden on CHWs, as well as dependency on hardware that may not always operate effectively 61 62. Visibility and visualisation of data, especially at lower levels, have the potential to change the way stakeholders use information to make decisions and influence community understanding of program impacts 63 64.…”
Section: Resultsmentioning
confidence: 99%